Bright Light Therapy in Parkinson's Disease: An Overview of the Background and Evidence - Sonja Rutten; Chris Vriend; Odile A. van den Heuvel; Jan H. Smit; Henk W. Berendse; Ysbrand D. van der Werf (Parkinson's Disease)
Sleep disorders are common in Parkinson's disease (PD) and seem to be strongly associated with depression. It has been suggested that sleep disorders as well as depression are caused by a disturbed circadian rhythm. Indeed, PD patients are prone to misalignment of their circadian rhythm due to various factors, and many patients with PD display a phase advance of their circadian rhythm. Current treatment options for sleep disorders and depression in patients with PD are limited and can have serious side effects; alternative treatments are therefore badly needed. Bright light therapy (BLT) restores circadian rhythmicity effectively in mood- and sleep-disturbed patients without PD. The few studies that focused on the efficacy of BLT in patients with PD demonstrated a positive effect of BLT not only on sleep and mood but also on motor function. More research on the neurobiology and efficacy of BLT in PD is warranted.